Highly efficient, low-temperature hydrogen release from perhydro-benzyltoluene using reactive distillation - Geißelbrecht, Michael; Mrusek, Stephan; Mueller, K.; Preuster, P.; Bösmann, Andreas; Wasserscheid, Peter (Energy and Environmental Science, 2020)
The need to supply significant amounts of heat at the high temperature level required thermodynamically for cycloalkane dehydrogenation has so far been seen as the main hurdle to bring the otherwise highly attractive Liquid Organic Hydrogen Carrier (LOHC) technology to broad technical use. The LOHC technology promises infrastructure-compatible storage and transport of hydrogen in chemically bound form,e.g.for long-term energy storage, global energy logistics and heavy-duty mobility. Our contribution shows that hydrogen release from the hetero-atom free, pure hydrocarbon LOHC compound perhydro-benzyl toluene is possible at temperatures down to 200 degrees C, if the operation is carried out in a reactive distillation column under reduced pressure. Such low temperature dehydrogenation of hydrocarbon-based LOHC systems facilitates heat integration with waste heat sources and the energetic use of the released hydrogen considerably, and this will greatly enhance the attractiveness of LOHC-based hydrogen storage for many applications.
CRIS-Team WoS Importer:2020-10-02